Multi-Modal Acoustic Flow Decomposition Examined in a Hard Walled Cylindrical Duct - WEYNA, Stefan; MICKIEWICZ, Witold (Archives of Acoustics, 2014)
Flow fields could be of great interest in the study of sound propagation in aeroengines. For ducts with rigid boundaries, the fluid-resonant category may contribute significantly to unwanted noise. An understanding of the multi-modal propagation of acoustic waves in ducts is of practical interest for use in the control of noise in, for example, aero-engines, automotive exhaust and heating or ventilation systems. The purpose of our experiments was to test the acoustic energy transmission of duct modes based on studies carried out by the sound intensity technique. Sound intensity patterns in circular duct are discussed of modal energy analysis with particular reference to proper orthogonal decomposition and dynamic mode decomposition. The authors try to justify some advantages of the sound intensity experimental research in this area. In the paper, the wide-band sound signal propagated from source approximated with loudspeaker in hard-walled duct is imaged using a sound intensity - based approach. For a simple duct geometry, the sound intensity field is examined visually and by performing a modal decomposition greater insight into the acoustic structures is obtained. The image of sound intensity fields below and above “cut-off” frequency region are found to compare acoustic modes which might resonate in duct.